2014
DOI: 10.1590/0034-737x201461050009
|View full text |Cite
|
Sign up to set email alerts
|

Resistência de biótipos de arroz-vermelho aos herbicidas imazapyr + imazapic e alternativas de controle

Abstract: O uso intenso de herbicidas com o mesmo mecanismo de ação na cultura do arroz (Oryza sativa L.) tem selecionado biótipos resistentes, como, por exemplo, o arroz-vermelho (planta daninha) resistente aos herbicidas imidazolinonas. Por essa razão, este trabalho foi desenvolvido com o objetivo de avaliar a resistência de arroz-vermelho ao herbicida imazapyr + imazapic, na região sul do Rio Grande do Sul, e o controle do biótipo resistente de arroz-vermelho com os herbicidas alternativos clethodim e glyphosate. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Regarding the resistance of red rice seedlings, after receiving the application of the dose of 140g of the herbicide Imazapyr (Kifix®), when they were at the v3 stage, it was observed that all plants were resistant to application, regardless of the cultivation system used. This reflects the continued use of the same chemical control technology, without rotation of mechanisms of action, which causes them to be lost and the return to pre-germinated cultivation is the only viable way out (RUBIN et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the resistance of red rice seedlings, after receiving the application of the dose of 140g of the herbicide Imazapyr (Kifix®), when they were at the v3 stage, it was observed that all plants were resistant to application, regardless of the cultivation system used. This reflects the continued use of the same chemical control technology, without rotation of mechanisms of action, which causes them to be lost and the return to pre-germinated cultivation is the only viable way out (RUBIN et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The use of herbicides for weed control has been one of the most widely used methods in irrigated rice crops. The use of chemical control combined with other control systems helps to reduce weed competition early in the crop cycle (Rubin et al, 2014).…”
Section: Chemical Controlmentioning
confidence: 99%
“…This can be explained by the fact that a portion of farmers invest in soybean production rather than rice production due to the lower cost (Conceição et al, 2017;Júnior, 2019). In addition, weed infestations resistant to current methods of control (Rubin et al, 2014) and blast disease caused by the fungus Magnaporthe oryzae (Barr) Couch [anamorphic Pyricularia oryzae (Cav.)] (Prabhu et al, 2009) contribute to the difficulty of producers to remain in business.…”
Section: Introductionmentioning
confidence: 99%
“…The arrival of the Clearfield ® technology in Brazil, in the early 2000s, allowed using herbicides from the imidazolinones chemical group (acetolactate synthase inhibitors -ALS) in the irrigated rice crop, thus becoming the main tool for controlling these weed species. However, the great selection pressure caused by continuously using these herbicides caused a rapid increase in the biotypes number of weedy rice (Rubim et al, 2014;Burgos et al, 2014;Dauer et al, 2018) and barnyardgrass (Eberhardt et al, 2016;Rouse et al, 2018) resistant to this herbicides group.…”
Section: Introductionmentioning
confidence: 99%